A new photosafety screening strategy based on in chemico photoreactivity and in vitro skin exposure for dermally-applied chemicals. (15th December 2019) - Iyama, Yosuke; Sato, Hideyuki; Seto, Yoshiki; Onoue, Satomi
Highlights: A new photosafety screening system consists of in chemico and in vitro tests. An in vitro skin permeation test was firstly applied to the screening system. In chemico photoreactivity and in vitro skin exposure of compounds were evaluated. The phototoxic risk was predicted by both photoreactivity and skin exposure data. The predicted phototoxic risk was mostly in agreement with in vivo phototoxicity. Abstract: This study involved an attempt to establish a new photosafety screening system for dermally-applied chemicals consisting of a reactive oxygen species (ROS) assay and an in vitro skin permeation test. The ROS assay was undertaken to evaluate photoreactivity of six test compounds, acridine (ACD), furosemide (FSM), hexachlorophene (HCP), 8-methoxypsoralen (MOP), norfloxacin (NFX), and promethazine (PMZ), and the in vitro skin permeation test was conducted to obtain steady-state concentration ( C ss ) values of test compounds in removed rat skin. All test compounds were photoreactive based on ROS generation under simulated sunlight exposure. In particular, ROS generation from ACD was high compared with other test compounds, and photoreactivity of ACD was deduced to be potent. The C ss values of ACD, HCP, MOP, and PMZ were over 50 μg/mL, and skin exposure to FSM and NFX was found to be extremely low. Upon these findings, ACD was judged to be highly phototoxic. The rank for phototoxic risk of test compounds based on photoreactivity and in vitro skin exposure was mostly in agreement with outcomes on their in vivo phototoxicity in rats. The proposed strategy, an alternative to animal testing, would be efficacious for photosafety evaluation of drug candidates in early stages of pharmaceutical development.